Phylogenetics and genomic variation of Hepatocystis isolated from shotgun sequencing of wild primate hosts. - Paige E Haffener; Helena D Hopson; Alejandra Herbert-Mainero; Anayansi Ramirez; Ellen M Leffler (PLoS Pathogens)
Hepatocystis are apicomplexan parasites nested within the Plasmodium genus that infect primates and other vertebrates, yet few isolates have been genetically characterized. Using taxonomic classification and mapping characteristics, we searched for Hepatocystis infections within publicly available, blood-derived whole genome sequence (WGS) data from 326 wild non-human primates (NHPs) in 17 genera. We identified 37 Hepatocystis infections in Papio cynocephalus (yellow baboons) and four species of Chlorocebus monkeys (grivets, green monkeys, vervet monkeys, and malbroucks) sampled from locations in west, east, and south Africa. Hepatocystis cytb sequences from Papio and Chlorocebus hosts each clustered within host species among previously reported isolates from other NHP taxa. Utilizing the low-coverage sequence data (0.11-0.76X per sample) recovered across the nuclear Hepatocystis genome, we identified 349,893 polymorphic sites. Principle components analysis based on genotype likelihoods across all samples showed evidence for population structure by primate host species. Across the genome, windows of high SNP density revealed candidate hypervariable loci including Hepatocystis-specific gene families possibly involved in immune evasion and genes that may be involved in adaptation to their insect vector and hepatocyte invasion. Overall, this work demonstrates how WGS data from wild NHPs can be leveraged to study the evolution of apicomplexan parasites and potentially test for association between host genetic variation and parasite infection.